Interaction between Mycobacterium avium strains and human and avian host cells - Issa, Nawzat (2016)
Avian mycobacteriosis is a chronic infectious disease of poultry caused by different mycobacteria belonging to the M. avium-intracellular complex but primarily subspecies avium. Data on the interaction between M. avium and avian cells is very limited. This study describes the invasion and intracellular survival of M. avium isolates from both chicken and calf sources infecting THP-1-human-like macrophages and HD11 avian macrophage-like cells. There was strain to strain variation in initial invasion between the isolates tested but this variation was independent of the host-source of isolate. Invasion of the host cells was increased in the presence of host specific serum, both calf and poultry serum enhanced M. avium invasion of avian cells not seen with human cells and human serum increased the bacterial invasion of human cells, but not seen with avian cells. Both mannose and scavenger receptors were the dominant receptor for uptake of bacteria in human (THP-1) and avian (HD11) cells respectively. Simultaneous blocking mannose-, scavenger- and complement receptors did not result in complete inhibition of bacterial invasion in both cell lines suggesting that the phagocytic receptors are not working independently and may cooperate to interact with diverse ligands on the bacterial surface simultaneously for optimal binding and internalization. Invasion was both actin and tubulin dependent. The inhibitory effects of combinatory blocking of receptors and cell cytoskeleton are synergistic on the bacterial invasion of both THP-1 and HD11 cells. Post-invasion, nitric oxide and reactive oxygen species played different roles in the intracellular bacterial survival. Nitric oxide production was correlated with a reduction in intracellular survival of M. avium. In contrast, induction of reactive oxygen species enhanced M. avium survival and inhibition of reactive oxygen species using antioxidants led to a significant reduction in bacterial survival. Entry via specific receptors could have significant effect on the bacterial survival within the host cells. M. avium infection of HD11 can lead to disruption of tubulin and subsequent inhibition of both the phagosomal acidification and lysosome fusion so enhancing intracellular survival of the bacterial strains within the infected cells. In conclusion, the differences observed between bacterial isolates and host cells being infected suggest subtle differences in initial invasion and survival mechanisms between different isolates and hosts cells some of which are strain dependent and some are host cell dependent.